Concentration, sources and light absorption characteristics of dissolved organic carbon on a medium-sized valley glacier, northern Tibetan Plateau - F. Yan; S. Kang; C. Li; Y. Zhang; X. Qin; Y. Li; X. Zhang; Z. Hu; P. Chen; X. Li; B. Qu; M. Sillanpää (The Cryosphere, 2016)
Light-absorbing dissolved organic carbon (DOC) constitutes a major part of the organic carbon in glacierized regions, and has important influences on the carbon cycle and radiative forcing of glaciers. However, few DOC data are currently available from the glacierized regions of the Tibetan Plateau (TP). In this study, DOC characteristics of a medium-sized valley glacier (Laohugou Glacier No. 12, LHG) on the northern TP were investigated. Generally, DOC concentrations on LHG were comparable to those in other regions around the world. DOC concentrations in snow pits, surface snow and surface ice (superimposed ice) were 332 ± 132, 229 ± 104 and 426 ± 270 µg L−1, respectively. The average discharge-weighted DOC of proglacial stream water was 238 ± 96 µg L−1, and the annual DOC flux released from this glacier was estimated to be 6949 kg C yr−1, of which 46.2 % of DOC was bioavailable and could be decomposed into CO2 within 1 month of its release. The mass absorption cross section (MAC) of DOC at 365 nm was 1.4 ± 0.4 m2 g−1 in snow and 1.3 ± 0.7 m2 g−1 in ice, similar to the values for dust transported from adjacent deserts. Moreover, there was a significant relationship between DOC and Ca2+; therefore, mineral dust transported from adjacent arid regions likely made important contributions to DOC of the glacierized regions, although contributions from autochthonous carbon and autochthonous/heterotrophic microbial activity cannot be ruled out. The radiative forcing of snow pit DOC was calculated to be 0.43 W m−2, demonstrating that DOC in snow needs to be taken into consideration in accelerating melt of glaciers on the TP.